Effectiveness of the 23-valent pneumococcal polysaccharide vaccine against vaccine serotype pneumococcal pneumonia in adults: A case-control test-negative design study - Lawrence, Hannah; Pick, Harry; Baskaran, Vadsala; Daniel, Priya; Rodrigo, Chamira; Ashton, Deborah; Edwards-Pritchard, Rochelle C.; Sheppard, Carmen; Eletu, Seyi D.; Litt, David; Fry, Norman K.; Rose, Samuel; et al. (PLOS Medicine, 2020)
Background Vaccination with the 23-valent pneumococcal polysaccharide vaccine (PPV23) is available in the United Kingdom to adults aged 65 years or older and those in defined clinical risk groups. We evaluated the vaccine effectiveness (VE) of PPV23 against vaccine-type pneumococcal pneumonia in a cohort of adults hospitalised with community-acquired pneumonia (CAP). Methods and findings Using a case-control test-negative design, a secondary analysis of data was conducted from a prospective cohort study of adults (aged ≥16 years) with CAP hospitalised at 2 university teaching hospitals in Nottingham, England, from September 2013 to August 2018. The exposure of interest was PPV23 vaccination at any time point prior to the index admission. A case was defined as PPV23 serotype-specific pneumococcal pneumonia and a control as non-PPV23 serotype pneumococcal pneumonia or nonpneumococcal pneumonia. Pneumococcal serotypes were identified from urine samples using a multiplex immunoassay or from positive blood cultures. Multivariable logistic regression was used to derive adjusted odds of case status between vaccinated and unvaccinated individuals; VE estimates were calculated as (1 − odds ratio) × 100%. Of 2,357 patients, there were 717 PPV23 cases (48% vaccinated) and 1,640 controls (54.5% vaccinated). The adjusted VE (aVE) estimate against PPV23 serotype disease was 24% (95% CI 5%–40%, p = 0.02). Estimates were similar in analyses restricted to vaccine-eligible patients (n = 1,768, aVE 23%, 95% CI 1%–40%) and patients aged ≥65 years (n = 1,407, aVE 20%, 95% CI −5% to 40%), but not in patients aged ≥75 years (n = 905, aVE 5%, 95% CI −37% to 35%). The aVE estimate in relation to PPV23/non-13-valent pneumococcal conjugate vaccine (PCV13) serotype pneumonia (n = 417 cases, 43.7% vaccinated) was 29% (95% CI 6%–46%). Key limitations of this study are that, due to high vaccination rates, there was a lack of power to reject the null hypothesis of no vaccine effect, and that the study was not large enough to allow robust subgroup analysis in the older age groups. Conclusions In the setting of an established national childhood PCV13 vaccination programme, PPV23 vaccination of clinical at-risk patient groups and adults aged ≥65 years provided moderate long-term protection against hospitalisation with PPV23 serotype pneumonia. These findings suggest that PPV23 vaccination may continue to have an important role in adult pneumococcal vaccine policy, including the possibility of revaccination of older adults.